Financial Development and Inclusion in the Caribbean - Li, Chuan; Wong, Joyce (Washington, D.C. : International Monetary Fund, 2018)
Many Caribbean financial systems are relatively well developed for their size but benefits are concentrated in a small part of the population. In several large countries, the financial development levels are below what is warranted by that country's own macroeconomic fundamentals. SMEs, in particular, remain severely credit constrained, and data to inform better analysis remains scarce. Using available data, this paper takes stock of the current state of financial development and inclusion in the Caribbean region and, based on a quantitative general equilibrium model, examines potential trade-offs between growth, inequality, and financial stability-all critical considerations when policies are designed. A case study for Jamaica is examined in detail.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet